Analisis Perbandingan Standar Pembuktian Pidana Indonesia-Amerika Serikat: Studi Alat Bukti DNA sebagai Bukti Tunggal - Mochammad Ferdinan Adzhani; Handar Subhandi Bakhtiar (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2025)
This study examines the legal standing of DNA evidence as a sole means of proof within the criminal justice systems of Indonesia and the United States. DNA, known for its scientific reliability and high accuracy in identifying perpetrators, has received substantial recognition in the United States. Under the “beyond a reasonable doubt” standard, DNA evidence in the U.S. can independently substantiate a conviction and serve as the sole basis for a guilty verdict. In contrast, Indonesia's evidentiary framework remains governed by the negatief wettelijk principle, which requires at least two valid pieces of evidence supported by the judge’s conviction to establish criminal liability. As a result, DNA evidence in Indonesia is generally considered corroborative rather than conclusive and cannot stand alone in court. This research adopts a normative juridical method, combining statutory analysis and conceptual interpretation to assess the legal treatment of DNA evidence in both jurisdictions. The findings emphasize the urgent need for Indonesia to reform its criminal procedure law to accommodate modern scientific evidence, such as DNA, as primary proof in specific cases. Recommendations include amending provisions in the Indonesian Criminal Procedure Code (KUHAP), enhancing forensic infrastructure, strengthening legal regulations, and improving the capacity of law enforcement personnel. With appropriate procedural safeguards and human rights protections, DNA evidence holds significant potential to be recognized as standalone proof within Indonesia’s criminal justice system. Keywords: DNA evidence, criminal evidence, Forensics